Structure-Based, Rational Design of T Cell Receptors - Zoete, Vincent; Irving, Melita; Ferber, Mathias; Cuendet, Michel; Michielin, Olivier (Frontiers in Immunology, 2013)
Adoptive cell transfer using engineered T cells is emerging as a promising treatment for metastatic melanoma. Such an approach allows one to introduce TCR modifications that, while maintaining the specificity for the targeted antigen, can enhance the binding and kinetic parameters for the interaction pMHC. Using the well-characterized 2C TCR/SIYR/H-2K(b) structure as a model system, we demonstrated that a binding free energy decomposition based on the MM-GBSA approach provides a detailed and reliable description of the TCR/pMHC interactions at the structural and thermodynamic levels. Starting from this result, we developed a new structure-based approach, to rationally design new TCR sequences, and applied it to the BC1 TCR targeting the HLA-A2 restricted NY-ESO-1157-165 cancer-testis epitope. 54% of the designed sequence replacements exhibited improved pMHC-binding as compared to the native TCR, with up to 150 fold increase in affinity, while preserving specificity. Genetically-engineered CD8+ T cells expressing these modified TCRs showed an improved functional activity compared to those expressing BC1 TCR. We measured maximum levels of activities for TCRs within the upper limit of natural affinity. Beyond the affinity threshold at KD < 1 μM we observed an attenuation in cellular function. We have also developed a homology modeling-based approach, TCRep 3D, to obtain accurate structural models of any TCR-pMHC complexes. We have complemented the approach with a simplified rigid method to predict the TCR orientation over pMHC. These methods potentially extend the use of our TCR engineering method to entire TCR repertoires for which no X-ray structure is available. We have also performed a steered molecular dynamics study of the unbinding of the TCR-pMHC complex to get a better understanding of how TCRs interact with pMHCs. This entire rational TCR design pipeline is now being used to produce rationally optimized TCRs for adoptive cell therapies of stage IV melanoma.